Storage behaviour of exotic potato genotypes and hybrid clones under natural condition - Sajeda Akhter; Md. Monirul Islam; Laila Naher; M. Shamshul Alam; M. Majida khatum; Umi Kalsom Yusof (2014)
An experiment was conducted to evaluate the storability of hybrid clones and